Can you expect those with status to be ethical? The effects of status on trust. Issue 6 (18th August 2021) - Soderberg, Andrew T.; Howe, David
ABSTRACT: This research examines the trust and expectations people have for individuals with varying levels of status. Specifically, we predicted that people will have a greater amount of trust for individuals whom they perceive to have high (vs. low) status. Furthermore, we predicted that this positive effect of status on trust occurs because high-status individuals are viewed as less likely to engage in unethical behavior. We found evidence in two experimental laboratory studies and one survey study for some of our hypotheses. An agenda for future research is suggested, including a discussion of the practical and theoretical implications of these findings.